Mitigation of the bullwhip effect considering trust and collaboration in supply chain management: a literature review - Kaibara de Almeida, Marly Mizue [UNESP]; Silva Marins, Fernando Augusto [UNESP]; Pedro Salgado, Andreia Maria [UNESP]; Almada Santos, Fernando Cesar; Silva, Sergio Luis da (Springer, 2015)
The aim of this paper is to provide results of trust and collaboration that lead to the mitigation of the bullwhip effect in supply chain management through a systematic literature review. The criterion for its inclusion in the sample of papers was that at least two reviews of the respective subfields were published in peer-reviewed journals between 1990 and 2014. A total of 24 articles were selected. The analysis found that few studies focused on addressing behavioral aspects to reduce the bullwhip effect. Most of them focused on operational and quantitative aspects. These results indicate the need for studies on behavioral aspects in mitigating the bullwhip effect, where trust and collaboration among those involved in the supply chain need to be developed and organized.
Keywords: Supply chain management; Bullwhip effect; Trust; Collaboration